Reuse of substrate in the protected cultivation of muskmelon - Vargas, Pablo Forlan [UNESP]; Cardoso, Atalita Francis [UNESP]; Charlo, Hamilton César De Oliviera; Castoldi, Renata; Braz, Leila Trevisan [UNESP] (FapUNIFESP (SciELO), 2021)
Melon is a vegetable of great socioeconomic importance, and its cultivation is carried out under different production systems. The protected cultivation of melon can be carried out in coconut shell fiber, which is a substrate widely used in olericulture, but little information is available regarding its continuous use in more than one cultivation cycle. Therefore, this study aimed to evaluate the performance of muskmelon hybrids as a function of the reuse of coconut shell fiber with fertigation in a protected environment. The experiment was carried out in a greenhouse from March to July 2008 and designed in randomized blocks in a 2×3 factorial arrangement, with four replications. The factors consisted of two hybrids (‘Bonus 2’ and ‘Fantasy’) and three types of substrate (S1: new coconut shell fiber; S2: coconut shell fiber reused once in sweet pepper cultivation; and S3: coconut shell fiber reused twice, i.e., first in sweet pepper cultivation and then in melon cultivation). Transverse and longitudinal fruit diameter, fruit shape index, transverse and longitudinal locule diameter, locule shape index, peduncle insertion diameter, mesocarp thickness, firmness, skin netting, fresh mass, soluble solids, titratable acidity, pH, and yield were evaluated after harvest. Reusing twice the coconut shell fiber as a substrate did not affect the agronomic and physicochemical characteristics of the hybrids Bonus 2 and Fantasy.
Reuso de substrato no cultivo de meloeiro reticulatus sob cultivo protegido
Keywords: Cucumis melo; Fertigation; Substrate; Yield